Cancer incidence and mortality after a first-ever venous thrombosis: a cohort study in northern Sweden - Lovisa Hägg; Felicia Ehrs; Marcus Lind; Magdalena Johansson (Thrombosis Journal)
Abstract Background Venous thromboembolism (VTE) has a high mortality rate and can be the first manifestation of cancer. We investigated the incidence of cancer after first-ever VTE and the association between VTE and all-cause mortality. Methods A Swedish cohort study that included 105,997 participants without previous cancer who underwent a health examination from 1985–2014 was conducted. Manually validated first-ever VTE events, incident cancer according to the Swedish cancer registry, and mortality were registered. Participants were followed until September 5, 2014. Results The mean age at inclusion was 46.2 years, and 50.3% of participants were female. We identified 1303 persons in the cohort with a VTE and no previous cancer. Among these, 179 (13.7%) were diagnosed with cancer after the VTE event, resulting in a cancer incidence of 26.4 (95% CI 22.8–30.6) cases per 1000 person-years. The incidence was highest during the first 6 months after the VTE. In the study population, VTE was associated with an increased risk of cancer (HR 1.95 [95% CI 1.67–2.29] in a multivariable model). VTE was also associated with an increased risk of death (HR 6.30 [95% CI 5.82–6.81]) in a multivariable model). There was an interaction between sex and VTE in relation to both risk of cancer and mortality, with a stronger association in women. Conclusions The incidence of cancer is high after first-ever VTE, especially close to the VTE event. VTE seems to be a stronger risk marker in women than in men for both cancer and death.